Community Supervision and Employment. Issue 1 (May 2022) - Capece, Jesse
Evidence suggests that steady employment is a key component in reducing the likelihood that people under community supervision will return to prison. Largely unexplored, however, is the extent to which employment outcomes and self-perceptions of employability among people under community supervision are affected by stipulations mandated upon release from prison. These stipulations include measures like visits with a probation office, court appearances, or drug and mental health treatments. This article review research on the relationship between the stipulations of community supervision and employment outcomes. It presents evidence from a new study that explores relationships between release stipulations, probation officer support, feelings of employability, and employment outcomes. The new evidence suggests that there is a negative relationship between community supervision and employment outcomes and perceptions of employability. I argue for alternative policies that could productively reshape community supervision.